Ethical Leadership in the Field of Education in Europe: A Comparative Analysis (European Journal of Education, 2023)
The purpose of this research is to explore the characteristics of ethical leadership in in the field of education in Europe. In an era, when there are no transcendental principles and universally accepted values and, within organizations, a mainly “situational” and “procedural” ethics has been developed (Voyé, 1999), educational mission, goals and procedures are changing. Thus, it could be extremely challenging to explore aspects of educational leadership that are not considered necessarily self-evident, maintaining at the same time a critical and skeptical attitude regarding power relations and the promotion of moral values and democratic processes at school. The present research was carried out in Greece, Great Britain, Germany, Italy, France and Spain and, the sample consisted of 451 primary and secondary education teachers. The findings of this research demonstrated that, according to teachers’ perceptions, principals at schools- in carrying out their duties- have to develop responsibility and moral values so as not to deviate from the main goals of education, which are system’s eudaimonia through the all-round development of the future citizens of a democratic society (Goldring & Greenfield, 2002). More specifically, teachers from all participating countries affirmed that educational leaders put the emphasis– to a great extend- on core values such as honesty, sincerity, integrity, altruism, trust, rewarding ethical contribution and moral responsibility.